Analisis Pengelolaan Badan Usaha Milik Desa Menggunakan Interpretive Structural Modelling - Agni Grandita Permata Sari (Institut Pemerintahan Dalam Negeri, 2021)
The Central Government and West Java Province are intensively issuing policies to increase village empowerment, especially since village funds were distributed in 2015. Although these funds have positive implications for increasing the number of BUMDes, in general, the impact of BUMDes has not been too significant for the increase of the village's original income (PADes). West Java Province as a province that is very aggressively launching programs for villages development does not have BUMDes with ‘Big’ and ‘Advanced’ status, and only one with ‘Mature’ status, namely BUMDes Niagara in Bandung Regency. This paper aims to know the management, to identify and to analyze the most influential actors, supporting and inhibiting factors, and the changes expected to improve the management of BUMDes Niagara in Bandung Regency. The method used is qualitative with an inductive approach. Data analysis used the Interpretive Structural Modeling (ISM) method. The results showed that the management of BUMDes Niagara was elitist in that the village head and BUMDes manager played a major role in the development of BUMDes. Furthermore, the constraint analysis shows that the low quality of human resources is the most dominant problem. On the other hand, the factor of village potential and the commitment of the village head are the supporting factors that are most decisive. The above conditions converge on the need for the involvement of other parties, especially the government in providing guidance and assistance to Niagara BUMDes.